El rock en Riobamba visto a través de sus actores, periodo 2016 - Ganán Oyervide, Byron Fernando (2016)
This research reveals several important aspects found on the rock in Riobamba. Results like; its relationship with the ecclesiastical life, their representatives in working fields and dissemination in the city. The rock itself as a culture reaches Riobamba in 1977 with the high school STAR (Santo Tomas Apostol Riobamba) forming its first bands as the estudiantina and therefore performing in concerts, all psyched for priests Luciano Bellini and Guillermo Mensi, both of European origin. Upon arrival, the rock had its heyday in the city, but years later would end up changing the public opinion, due to the poor performances of a small group of rockers. Since then riobambenos stigmatize it, cataloging it of criminals, drunks and drug addicts. Disregarding that currently, Ecuador has laws that pursue equity and equality in its inhabitants. Thus, to carry out the purpose of the constitution, institutions such as: The House of Culture Benjamin Carrion - Branch Chimborazo, the Direction of Culture and Heritage of Chimborazo and the Direction of Cultural Management, Recreation and Sport of the Autonomous Government decentralized of Riobamba, support this culture. To these are added, some existing media in the city, including; La Prensa and Los Andes newspapers, Andean and Sultana radios, and TVS channel 13, who claim to support and spread the rock, because this culture is considered part of the daily living of the citizens of Riobamba, except for the TV channel Ecuavisión channel 29, that mentions that the rock does not broadcast by the lack of material.